The Post-Duchamp Deal. Remarks on a few Specifications of the Word 'Art' - de Duve, Thierry (Filozofski vestnik, 2007)
The purpose of this paper is to offer some theoretical clarification of the word art in the wake of the reception of Duchamp's readymades and their acknowledgment by art history.It became clear in the sixties that it is now both technically possible and institutionally legitimate to make art from absolutely anything whatever.To this a priori possibility would like to give the term art in general. After which shall define three other terms which may help clarify our usage of the word art in the post-Duchamp situation: art, period; art altogether; and art itself. Their articulation is intended to lay the ground for an aesthetic theory of art adapted to our times.